Aberrant salience in cannabis-induced psychosis: a comparative study - Ricci, Valerio; Di Muzio, Ilenia; Ceci, Franca; Di Carlo, Francesco; Mancusi, Gianluca; Piro, Tommaso; Paggi, Andrea; Pettorruso, Mauro; Vellante, Federica; De Berardis, Domenico; Martinotti, Giovanni; Maina, Giuseppe (Frontiers in Psychiatry, 2024)
Background: Natural Cannabis (NC) and Synthetic Cannabinoids (SCs) use can increase the risk and exacerbate the course of psychotic disorders. These could be influenced by the Aberrant Salience (AS) construct. It refers to an excess of attribution of meaning to stimuli that are otherwise regarded as neutral, thereby transform them into adverse, dangerous, or mysterious entities. This leads the patient to engage in aberrant and consequently incorrect interpretative efforts concerning the normal perception of reality and its relationship with our analytical abilities. AS appears to play a significant role in the onset and perpetuation of psychotic disorders. The internal conflict arising from aberrant attributions of significance leads to delusional thoughts, ultimately culminating in the establishment of a self-sustaining psychosis.Aims: To examine the differences between psychoses course not associated with Cannabis use and those associated with NC-use and SCs-use, in terms of psychotic and dissociative symptoms, AS, global functioning and suicidal ideation.Methods: A sample of 62 patients with First Episode Psychosis (FEP) was divided into 3 groups: non Cannabis users (non-users, N=20); NC-users or rather Delta-9tetrahydrocannabinol (THC) users (THC-users, N=21); SCs-users, commonly referred to as SPICE-users (SPICE-users, N=20). Each group underwent assessments at the onset of psychotic symptoms, as well as at the 3-month and 6-month marks, utilizing a range of psychopathological scales. These included the Positive and Negative Syndrome Scale (PANSS) for investigating psychotic symptoms, the Global Assessment of Functioning (GAF) scale for assessing overall functioning, the Dissociative Experiences Scale (DES-II) for measuring dissociative symptoms, the Scale for Suicide Ideation (SSI) for evaluating suicidal ideation and the Aberrant Salience Inventory (ASI) scale for gauging AS.Results: SPICE-users showed more severe and persistent positive symptoms, while negative symptoms were mostly represented among non-users. Non-users showed better recovery than SPICE-users in global functioning. All groups showed a decrease in both ASI scores and subscale scores. SPICE-users exhibited higher global AS scores and less improvement in this aspect compared to other groups.Conclusions: This study may help understanding the role of AS in both non-substance-related and substance-induced psychosis. This knowledge may lead clinician to a better diagnosis and identify patient-tailored psychopharmacological treatment.